The wear and fatigue behaviours of hollow head & sodium filled engine valve. (December 2018) - Lai, Fuqiang; Qu, Shengguan; Duan, Yong; Lewis, Roger; Slatter, Tom; Yin, Lianmin; Li, Xiaoqiang; Luo, Huahuan; Sun, Ge
Abstract: Increasing performance of IC engines often leads to higher combustion temperatures causing premature failure of exhaust valves. This paper presents for the first time a tribological assessment of hollow head & sodium filled valves (HHSVs) produced using a new and novel manufacturing process. Tests were conducted on HHSVs using bespoke bench-top wear and fatigue apparatus and they survived defined durability tests. Compared to traditional solid valves; the highest temperature of the hollow stem & sodium filled valves decreased from 745 °C to 590 °C, the new design and manufacturing process did not adversely affect the classical wear mechanisms (e.g. oxidation accelerated adhesion) or the material loss magnitude, and the design of HHSVs gives a 16.1% reduction in mass. Highlights: A new manufacturing process for hollow head & sodium filled valves (HHSVs). The durability tests were conducted using bespoke bench-top apparatus. The material loss magnitude of HHSVs were compared to the solid valve. The temperature distributions comparison of solid valve and hollow stem valve. The valve and seat insert wear mechanisms are oxidation accelerated adhesion.